A laser–laser method for carbonate C and O isotope measurement, metrology assessment, and stratigraphic applications - Petitjean, Alban; Thomazo, Christophe; Musset, Olivier; Jovovic, Ivan; Sansjofre, Pierre; Kirsimäe, Kalle (Frontiers in Geochemistry, 2024)
The stable isotopic compositions of carbon and oxygen (δ13Ccarb and δ18Ocarb) measured from carbonates are widely used in geology, notably to reconstruct paleotemperatures and the secular evolution of the biogeochemical carbon cycle, to characterize limestone sediments diagenesis and to provide chemostratigraphy records. The standard technique used since the middle of the 20th century to measure C and O isotopic ratios is based on a wet chemical acid digestion protocol in order to evolve CO2 from carbonates, the latter being analysed by mass spectrometry and, more recently, infrared spectroscopy. A newly developed laser-based method aims to circumvent this chemical preparation step by producing CO2 via an instant and spatially resolved calcination reaction. We describe an evolution of the laser calcination benchtop system previously described and used as a proof of concept (Thomazo et al., 2021) toward a portable system and present the efficiency of this tool in performing carbon and oxygen isotope measurements from carbonate matrixes following standard evaluation metrology protocol. This metrological study explores: (i) the use of internal standards, (ii) inter-calibration with the traditional acid chemical preparation method, (iii) analysis of uncertainties using GUM and Anova methods. Using 15 different types of carbonate minerals encompassing a range of isotopic compositions VPDB between -18.6 and +16.06‰ and between -14.80 and -1.72‰ for 13Ccarb and 18Ocarb, respectively, we show that isotopic cross-calibration is verified for both carbon and oxygen and we demonstrate that the uncertainties (1) of the δ13Ccarb and δ18Ocarb measurements of laser-laser isotopic analysis are within 0.41and 0.68‰, respectively. The advantages of this method in time saving, and in-situ, spatially resolved and automated analysis are demonstrated by high-resolution chemostratigraphic analysis of a laminated lacustrine travertine sample.